Descrição ultraestrutural de espermatozoides a fresco e criopreservados de catetos (pecari tajacu linnaeus, 1758) - Bezerra, Luana Grasiele Pereira (2018)
The objective of the present work was to describe the ultrastructure of fresh and cryopreserved spermatozoa from collared peccaries by scanning (SEM) and transmission electron microscopy (TEM). Three adult males were submitted to electroejaculation and semen was immediately evaluated for motility, membrane integrity and functionality, chromatin integrity and morphology. Subsequently, the samples were cryopreserved in Tris extender plus egg yolk (20%) and glycerol (6%), thawed after one week and evaluated. Samples of fresh and frozen-thawed semen were combined in distinct pools that were processed for SEM and TEM,. After thawing, there was a decline in sperm motility, membrane integrity and functionality (P < 0.05), sperm morphology and chromatin integrity assessed by light microscopy were not significantly affected. Analysis by SEM revealed that collared peccaries’ sperm presents a flattened head in a paddle format, measuring 6.1 ± 0.1 μm in length and 3.8 ± 0.1 μm in width. Collared peccaries’ sperm had a long acrosome (4.3 ± 0.1 μm), presenting a clear demarcation across the post-acrosomal region, being delimited by a distended border, called the marginal thickening. Normal tails measured 38.1 μm, formed by an extensive midpiece with 15.5 μm in length. In frozen-thawed analysis by SEM and TEM detected presence of vesicles in the acrosome, loose plasma membrane, vacuolized mitochondria, dense fibers disorganized, and decondensed chromatin. In conclusion, we provide the first description of the ultrasctruture on sperm from collared peccaries. Moreover, SEM and TEM help us to identify some nanometric damage caused by freezing-thawing procedures, thus providing valuable information for the improvement of protocols used for biobanking formation